Factors related to the progression of Chronic Kidney Disease after two years of follow-up of stage 3 Chronic kidney Disease Patients - Noemi Esparza Martín; Santiago Suria González; Elvira Bosch Benítez- Parodi; Rita Guerra Rodríguez; Germán Pérez Suárez; César García Cantón (Archives of Renal Diseases and Management - Peertechz Publications, 2017)
Background:The problem of chronic kidney disease (CKD) progression is a panic and it is still inevitable. Patients  and  Methods: Prospective  observational  study  of factors  present  at  initial  evaluation  of  stage  3  CKD  patients proceeding  from  external  consultations  after  two  years  of follow-up. Exclusion criteria: Under 40 or older than 79 years old,  anemia,  previous  heart  or  hepatic  failure,  valvular  or  ischemic cardiopathy, arrhythmias, clinical arterial peripheral disease  or  immunosuppressive  treatment.  Inclusion  criteria: All  the  incidental  patients  who  wish  to  participate  between January,  2012  and  January,  2014.  The  study  was  approved  by the Committee of Ethics of Clinical Investigation.